ANALISIS KONSEP MATEMATIKA SEKOLAH DALAM PEMULASARAAN JENAZAH - Tsamara Banafsaj; Ahmad Yani T; Asep Nursangaji (UNIVERSITAS TANJUNGPURA, 2021)
This research aim to identify the elementary and junior high school mathematic concepts which included the funeral procession. The process of funeral procession that was researched included measuring and cutting the shroud, bathing the corpse, shrouding the corpse, praying the corpse, and burying the corpse. The method of this research is a qualitative, and the form of this research is a literature study. Then the data were collected using documents in the form of books, articles, and notes on the results of the funeral procession by the fardhu kifayah team of Ummu Al-Athiyyah Al-Anshoriyyah. Based on the Miles and Huberman analysis method, elementary and junior high school mathematical concepts are found in the funeral procession, namely rectangles, mixed arithmetic operations, addition, subtraction, multiplication, division, number sequences, sets, linear inequalities of one variable, line segments, vertical lines, horizontal lines, parallel lines, perpendicular lines, point outside the line, 180 degree angel, and cuboids.